Niepodległość . pismo polityczne, no. 77, 1988 - Kowalski, Józef (GP"N" Grupa Pisma "Niepodległość", 1988)
Creation and circulation: Some issues published in 30 cm. and 21 cm. format. Part of the print run in 1983 and 1984 printed in Kraków.